Incidence and risk factors of post-transplant diabetes mellitus among kidney transplant recipients: a retrospective study from a tertiary center in Saudi Arabia - Mutlaq Alotaibi; Najlaa Almalki; Manal E. Alotaibi; Majed Alosaimi; Monther Alazwari; Mohamed Hussein; Faisal Alhomayani; Abdulmajeed Alotaibi; Ameerah Bajaber; Fahad Bhutto; Abdulmajeed Algethami; Bassem A. Almalki (BMC Nephrology)
Abstract Background Post-transplant diabetes mellitus (PTDM) is a common metabolic complication following kidney transplantation, adversely affecting graft and patient outcomes. This study aims to identify the prevalence, risk factors, and clinical implications of PTDM among kidney transplant recipients at Alhada Armed Forces Hospital, Taif, Saudi Arabia. Methods We conducted a retrospective cohort study including adult kidney transplant recipients from January 1984 to December 2023, excluding patients with pre-existing diabetes. Data were extracted from electronic medical records, encompassing demographics, clinical characteristics, transplantation details, and laboratory parameters. PTDM was diagnosed based on the American Diabetes Association criteria. Statistical analyses included t-tests, multivariate logistic regression, chi-square tests, Mann-Whitney U test, and Fisher’s exact tests. Receiver operating characteristic (ROC) curve analysis determined optimal cutoff values for predictive variables. Results Of 228 kidney transplant recipients (64% males, mean age 47.2 ± 14.6 years), 54 (23.7%) developed PTDM. PTDM patients were significantly older (53.1 ± 12.9 vs. 45.4 ± 14.6 years, p < 0.001) and had higher BMI (27.0 ± 4.7 vs. 25.2 ± 5.4 kg/m², p = 0.023). Hypertension was a more frequent cause of ESRD in the PTDM group (24.1% vs. 6.3%, p = 0.006). Tacrolimus levels ≥ 7 ng/mL were associated with higher PTDM incidence (70% vs. 52%, p = 0.032). Hypomagnesemia and uACR were also higher in PTDM patients compared to non-PTDM. Multivariate logistic regression identified age, hypomagnesaemia, uACR ≥ 9, and tacrolimus levels > 7 as independent PTDM predictors (p < 0.05). Conclusions PTDM affects a substantial proportion of kidney transplant recipients, with older age, hypomagnesemia, increased uACR, and elevated tacrolimus levels emerging as key risk factors. Close monitoring and individualized immunosuppressive strategies may mitigate PTDM risk and improve post-transplant outcomes. Trial registration Not applicable. The study is not a clinical trial.